Productivity of Bali Female Cattle (Bos sondaicus) in Bumirestu, Dakaino and Akedaga Villages of East Halmahera Regency - Halifa Lidamona; Oktora Dwi Putranti; Yunus Syafie (Chalaza Journal of Animal Husbandry, 2021)
The current research aimed to determine Bali cattle's productivity in Bumirestu, Akedaga, and Dakaino Villages in East Halmahera Regency. This research was carried out in Bumirestu, Akedaga, and Dakaino Villages, East Halmahera Regency, for three months, from February to April 2018. A presurvey and field survey methods were applied to observe several variables: calf weaning, mothers mating after calving, estrus age after calving, first calving age, and body weight. Livestock productivity could be seen from the reproductive characteristics, the first calving age with 64% in Dakaino Village. Calf weaning with a percentage of 42.5% in Bumirestu Village, estrus age after calving with a percentage of 52% in Dakaino Village, parents were mating after giving birth with a percentage of 60% in Akedaga Village, and body weight by calculating the average of 288.71±17.55 in Dakaino Village. It was revealed that the factors that support the livestock productivity are the first calving age of the cattle was two years old, calf weaning was at 2-4 months old, the estrus age after calving was 30-60 days, and the parents were mated 60 to 90 days after calving.